Barrier on Strengthening Regional Innovation System (RIS) in Banten Province, Indonesia - Budiarto, M S; Bachrudin, D T (KnE Social Sciences, 2018)
The objective of this study is to identify the inhibiting factors to determine the strengthening of Regional Innovation System in Banten Province. Research method used is a descriptive qualitative method guided with previous research on barrier determinant factors. The findings show that the barrier determinant index ranked from the highest to the lowest point are Structure barrier value = 4.1, Innovation of the environment = 3.8, supporting research and development = 3.5, Human resources = 3.6, and Infrastructure = 3.1. The structure barrier become the main determinant factor in implementing RIS, meaning that there is poor synergy between stakeholders, less commitments, and misleading perception to RIS. Innovative environment index equals to 4.8, indicating low innovation activity, absence of formed cooperative between all the participants of the innovation process, lack of interest on innovation and uncertainty of economic results, underestimation of partnership networks, absence of brand that would form a regional cluster, inability to gain benefits from the combination of cooperative. The Human resources index equals to 3.6, meaning that the leadership, human capacity, professionalism, and responsibility toward RIS become determinant factors in the level of strengthening of RIS. Infrastructure index equals to 3.1, which is the lowest barrier index meaning that basic facilities and poor social amenities show the existing physical modal and social culture support toward RIS. It was supposed to link the opportunities and strong value by minimizing the barrier determinants value to determine the success of strengthening the implementation of Regional Innovation System. Keywords: barrier, Regional Innovation System, Banten Province